Preliminary studies on processing characteristics of smoked dried beef (kundi) at varying salt levels (2003)
The semitendinosus muscle used for the study was excised from the wholesale beef round and trimmed of all surface fat and connective tissue and chilled for 24 hours. Sizeable pieces within a weight range of 70-90 grams were cut. For every 250g of meat, dry salt (NaCI) was rubbed into the meat at 10,15 and 20% of the green weight. The salted meat pieces were left for 30 minutes to allow salt penetration. Three treatments were applied cum; boiling of salted meat for 30 minutes until uniform doneness was achieved. The second treatment involved broiling in the oven for 30 minutes till uniform doneness was attained while the third treatment involved smoking of fresh salted meat samples without boiling or broiling. The result showed that weight losses were considerable in all the treatments with increase in the salt levels although the results were not significantly different (P>0.05). It was also noted that although the shear force values obtained at the different salt levels were not significantly different (p>0.05), the values obtained increased as the weight loss increased. The addition of sodium chloride to meat was observed to cause a slight drop in the pH of meat.